2017
DOI: 10.1111/jam.13515
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory potential of a heat-killedLactobacillusstrain isolated from Kimchi on house dust mite-induced atopic dermatitis in NC/Nga mice

Abstract: The immunomodulatory function of L. brevis NS1401 may provide effective new therapeutics against AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…First, these organisms can increase the innate immune response, activate macrophages, and treat pathogenic bacteria by producing reactive oxygen species and lysosomes. Lactic acid bacteria can also activate the acquired immune system, activate B cells to secrete antibodies, and participate in body fluid immunity (Choi et al, 2017). In the early stage, we detected the surface hydrophobicity and adhesion of nine strains of lactic acid bacteria in vitro by BATH method, microscopic examination, plating method, and fluorescent labelling method and screened out two high-viscosity strains of L. salivarius and L. plantarum (Ren et al, 2014(Ren et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…First, these organisms can increase the innate immune response, activate macrophages, and treat pathogenic bacteria by producing reactive oxygen species and lysosomes. Lactic acid bacteria can also activate the acquired immune system, activate B cells to secrete antibodies, and participate in body fluid immunity (Choi et al, 2017). In the early stage, we detected the surface hydrophobicity and adhesion of nine strains of lactic acid bacteria in vitro by BATH method, microscopic examination, plating method, and fluorescent labelling method and screened out two high-viscosity strains of L. salivarius and L. plantarum (Ren et al, 2014(Ren et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, mouse eosinophils were found to take up the probiotic Lactobacillus reuteri . Using various mouse models of asthma and AD, probiotics like Lactobacillus fermentum and L rhamnosus were found to improve allergic inflammation associated with decreased eosinophil infiltration, although a direct effect of probiotic bacterial strains on eosinophils was not demonstrated in these studies …”
Section: Microbiota Regulating Cellular Players In Innate and Adaptivmentioning
confidence: 92%
“…Mouse treatment with SCFA results in the recruitment of bone marrow‐derived DC with impaired capacity to induce Th2 responses in the lung . Probiotics administered by gavage reduce the severity of allergic airway inflammation and AD through the reduction of eosinophil infiltration into the lung and skin, respectively…”
Section: Translational Implications Of Microbiotamentioning
confidence: 99%
“…Live bacteria present preventive and therapeutic effects on AD lesions, and heat-killed probiotic cells were also reported to alleviate allergic responses in animal models [23]. For example, oral administration of heat-killed Lactobacillus brevis ameliorated the symptoms of dust miteinduced AD in NC/Nga mice by enhancing Th1-prone immunity [24]. Investigations on Lactobacillus rhamnosus GG revealed that intracellular or cell wall components of LGG, such as lipoteichoic acid, exopolysaccharides, and hydrolytic peptidoglycan, potentially cause immunomodulatory effects [25].…”
Section: Ns8 Attenuates Systemic Immune Responsesmentioning
confidence: 99%